Apuntes en torno al TLC Centroamérica/Estados Unidos y sus implicaciones para la educación superior - Muñoz Varela, Luis (Universidad de Costa Rica, 2005)
El presente artículo tiene como propósito realizar una breve aproximación analítica a los aspectos que, en el marco de la propuesta de Tratado de Libre Comercio entre Centroamérica y Estados Unidos, conciernen o implican a la educación superior y, en especial, a la educación superior pública. El artículo aborda dos ejes de análisis. El primero de ellos, está referido específicamente a los lineamientos y estipulaciones que involucra el texto del TLC Centroamérica/Estados Unidos, en lo relativo a las implicaciones que derivan de esa propuesta para las instituciones de educación superior y, en particular, para la educación superior pública. El segundo eje, por su parte, consiste en una breve revisión de trabajos elaborados por especialistas en torno a los alcances que, en su caso, presentan para la educación superior algunas de las estipulaciones contenidas en el Acuerdo General sobre Comercio de Servicios (AGCS), de la Organización Mundial del Comercio. ABSTRACT: This article intends to make a brief analysis about the repercussions of the Free Trade Agreement between Central America and The United States (CAFTA) on the aspects concerning to the Higher education; especially, public higher education. There are two analysis approaches in this article. The first one deals specifically with the tendencies and regulations of the CAFTA in reference to its proposal to the high educational field. The second approach refers to a brief literary review about some specialists'; works related to the consequences to the higher education of some regulations contained in the Service Trade General Agreement by the World Commerce Organization. This article intends to make a brief analysis about the repercussions of the Free Trade Agreement between Central America and The United States (CAFTA) on the aspects concerning to the Higher education; especially, public higher education.  There are two analysis approaches in this article. The first one deals specifically with the tendencies and regulations of the CAFTA in reference to its proposal to the high educational field. The second approach refers to a brief literary review about some specialists’ works related to the consequences to the higher education of some regulations contained in the Service Trade General Agreement by the World Commerce Organization.